Defining the global health system and systematically mapping its network of actors - Steven J. Hoffman; Clarke B. Cole (BMC, 2018)
Abstract Background The global health system has faced significant expansion over the past few decades, including continued increase in both the number and diversity of actors operating within it. However, without a stronger understanding of what the global health system encompasses, coordination of actors and resources to address today's global health challenges will not be possible. Methods This study presents a conceptually sound and operational definition of the global health system. Importantly, this definition can be applied in practice to facilitate analysis of the system. The study tested the analytical helpfulness of this definition through a network mapping exercise, whereby the interconnected nature of websites representing actors in the global health system was studied. Results Using a systematic methodology and related search functions, 203 global health actors were identified, representing the largest and most transparent list of its kind to date. Identified global health actors were characterized and the structure of their social network revealed intriguing patterns in relationships among actors. Conclusions These findings provide a foundation for future inquiries into the global health system's structure and dynamics that are critical if we are to better coordinate system activities and ensure successful response to our most pressing global health challenges.